Brucella abortus antigen omp25 vaccines: Development and targeting based on Lactococcus lactis - Somaye Tirbakhsh Gouran; Abbas Doosti; Mohammad Saeid Jami (Veterinary Medicine and Science, 2023)
Abstract Background Most Brucella infections take place on mucosal membranes. Therefore, creating vaccinations delivered through the mucosa may be crucial for managing brucellosis. Consequently, we assessed the efficacy of a recombinant oral antigen delivery system based on Lactococcus lactis for Brucella abortus omp25 antigen. Method Oral vaccinations with L. lactis transformed with pNZ8148 variants encoding for omp25 (pNZ8148:omp25) and free‐pNZ8148 were administered to mice. On day 30, following immunization in animal groups, anti‐omp25‐specific IgG1 antibodies were assessed by the ELISA test. Additionally, nasal and bronchoalveolar lavages containing omp25‐specific secretory IgA (sIgA) were analysed by ELISA. ELISA test and real‐time PCR were also used to analyse cytokine responses up to 28 days following the last boost. In addition, the protective potential of L. lactis pNZ8148:omp25 vaccines was assessed in BALB/c mice by exposing them to the B. abortus strain. Results Based on the initial screening results, the omp25 protein was identified for immunogenicity because it had the maximum solubility and flexibility and antigenic values of 0.75. The produced plasmid was digested using KpnI and XbaI. By electrophoretic isolation of the digestion fragments at 786 bp, the omp25 gene, the successful production of the recombinant plasmid, was confirmed. Antigen expression at the protein level revealed that the target group generated the 25 kDa‐sized omp25 protein, but there was no protein expression in the control group. Fourteen days after priming, there was a considerable amount of omp25‐specific IgG1 in the sera of mice vaccinated with pNZ8148–Usp45–omp25–L. lactis (p < 0.001 in target groups compared to the phosphate‐buffered saline control group). IFN‐γ and TNF‐α levels were more significant in samples from mice that had been given the pNZ8148–Usp45–omp25–L. lactis and IRBA vaccinations, in samples taken on days 14 and 28, respectively (p < 0.001). The pNZ8148–Usp45–omp25–L. lactis and IRBA immunization groups had significantly greater IL‐4 and IL‐10 transcription levels than the other groups. The spleen portions from the pNZ8148–Usp45–omp25–L. lactis and IRIBA vac group had less extensive spleen injuries, alveolar oedema, lymphocyte infiltration and morphological damage due to the inflammatory process. Conclusion Our study offers a novel method for using the food‐grade, non‐pathogenic and noncommercial bacterium L. lactis as a protein cell factory to produce the novel immunogenic fusion candidate romp25. This method offers an appealing new approach to assessing the cost‐effective, safe, sustainable, simple pilot development of pharmaceutical products.